MODELING OF SATELLITE CHANNEL FOR TRANSMISSION OF ADS-B MESSAGES - Харченко, В.П.; Барабанов, Ю.М.; Грехов A.M.; Газнюк, М.О.; Колчев, М.В. (Proceedings of National Aviation University (archive), 2012)
For surveillance over air traffic the system for reception of ADS-B signals was built. For this purpose the antenna, the receiver of ADS-B signals, the decoder were made and the software for computer was installed. Airplanes on a distance up to 160 km and heights up to 12 000 m were observed. This system has small "blind funnel" and allows to trace airplanes practically "over itself". The system is used in educational process and for performance of student’s scientific researches.